Skin surface roughness measurement for assessing scaliness of psoriasis lesions - Hani, A.F.M. (CRC Press, 2014)
The skin is comprised of several main layers. The epidermis is the outer layer and the dermis at the inner part. The next layer located under the epidermis is the subcutaneous layer. The epidermis is made by the stacking of skin cells: the living cells in the inner layer and the dead cells in the outer layer. In this inner layer the skin cells are produced and matured to replace the dead skin cells. The dead skin cells at the outermost epidermis layer form a tough, flexible, and waterproof mantle on the skin surface. These cells are shed periodically from the skin surface as keratinous scales. Â© 2014 by Taylor & Francis Group, LLC.